Offset printing results analysis of different based inks in cardboard pack-aging production - ŞİMŞEKER, OSMAN (SCIENDO, 2021)
The main raw material of paper and cardboard used in packaging is cellulose. Cardboard packages made of cardboard, which can be produced in much different quality and weight, are obtained in numerous shapes and appearances(1, 2). Paper and cardboard packaging are among the most economical packaging types. Using less raw materials, more durable but thin, light, economical cardboard is produced(2, 3). In this study, under equal printing conditions, test prints were made on cardboard substrates (for cardboard pack-aging) with mineral oil based, vegetable oil (soy oil) based and UV cured inks used for the printing of the same images. After these prints, the properties of mineral oil, vegetable oil and UV ink; the effect on the print results was measured from different ways (Chroma*, Print density, unprinted surface Gloss 75 degrees, Print Gloss 60 degrees). At the same time, the visual differences between the print results were determined by the optical imaging (SEM) method and were examined by the elemental analysis method.
Keywords: Mineral Oil; Soy Oil; UV Ink; Printability; Cardboard Packaging